Recurrence functions are used to preedict the subsequent value in a sequence. The fourth term of the sequence based on the recurrence relation is 25
Given the recurrence relations according to the question
s(1) = 2 and
s(2)=3
s(k) =s(k-1)+2s(k-2)+6
If s(1) = 2, hence;
s(3) =s(3-1)+2s(3-2)+6
s(3) = s2 + 2s1 + 6
s(3) = 3 + 2(2) + 6
s(3) = 13
Determine the fourth term:
s(4) =s(4-1)+2s(4-2)+6
s(4) = s3 + 2s2 + 6
s(4) = 13 + 2(3) + 6
s(4) = 25
Hence the fourth term of the sequence based on the recurrence relation is 25
Learn more on recurrence relation here: https://brainly.com/question/10636530